2020
DOI: 10.1002/jrs.5935
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic characterization of commercial pigments for pictorial retouching

Abstract: A set of 27 commercially available pigments by Kremer Pigmente (Aichstetten, Germany), including traditional and synthetic compounds, has been characterized in detail from a chemical and mineralogical point of view in the frame of a wide research project about pigments and colorants involving different spectroscopic techniques such as reflectance spectroscopy (in both visible and near‐infrared intervals), Fourier‐transform infrared spectroscopy (in both attenuated total reflection and reflection modes), and Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 56 publications
(92 reference statements)
2
25
0
Order By: Relevance
“…2a) shows five reflectance minima (absorbance maxima) at 445, 484, 545, 584 and 635 nm, respectively. Concurrent Raman investigation showed, in accordance with the company data sheets, peaks referable to willemite, an orthosilicate containing both Zn and Co. 2 The position here identified for these absorptions are in accordance with literature, reporting willemite values at 490, 540, 590, and 640 nm. 31,33 The attributions for the three main minima (545, 584, and 635 nm) correspond to those reported for the cobalt-based pigments discussed in the following (44100, 44151).…”
Section: Blue and Violet Huessupporting
confidence: 87%
See 3 more Smart Citations
“…2a) shows five reflectance minima (absorbance maxima) at 445, 484, 545, 584 and 635 nm, respectively. Concurrent Raman investigation showed, in accordance with the company data sheets, peaks referable to willemite, an orthosilicate containing both Zn and Co. 2 The position here identified for these absorptions are in accordance with literature, reporting willemite values at 490, 540, 590, and 640 nm. 31,33 The attributions for the three main minima (545, 584, and 635 nm) correspond to those reported for the cobalt-based pigments discussed in the following (44100, 44151).…”
Section: Blue and Violet Huessupporting
confidence: 87%
“…29 The FORS technique was not able to detect undeclared compounds in the Azurite pigment powder such as fillers, in particular quartz, identified by Raman analysis. 2 Therefore, reflectance and Raman spectroscopy resulted complementary techniques compensating each other in the obtainable information. Specifically, because of the employed laser source wavelength (785 nm), the Raman spectrum of pigment 10207 did not reveal any feature referable to the coloring phase, being Azurite, and the same applies also to Malachite (see discussion below).…”
Section: Blue and Violet Huesmentioning
confidence: 99%
See 2 more Smart Citations
“…Corradini et al [ 13 ] have reported the spectroscopic characterization (Raman, visible and near infrared reflectance, and FTIR in the ATR mode spectroscopies together with high‐resolution microphotography) of 27 commercial pigments currently used for retouching purposes. Repeatability was checked by measuring five spots for each pigment using μ‐Raman spectroscopy.…”
Section: Characterization Of Materialsmentioning
confidence: 99%